(3ZGjI GdCed aj TQM GdLeds - (3CHheMeO YHO GdYRjR Hf EHQGgje Hf CMeO GdbQTj GdJejej GdJhfSj (B((3GdeZQHj(B) (3GdeYQha H` GHf HRjRIs; (3GdRLGLj , CHh GdbGSe,J (B337 (3g` s
(3ChdgG (B:s
(3hHYO, abO QZH ef MSfJ eSGYOJg, hUdMJ ELGHJg aj Cf Cedj Ydjg s
(3BNQgG (B:s
(3aGSJaJ EHQGgje Ydjg GdSdGe aCaJGgG HCf NaVJgG hKHJ CPfjgG, hgPG BNQ GdcJGH s
(3fbW GdaGA hGMOI ef JMJgG hGdbGa hGMOI ef ahbgG cGdNW GdeZQHjs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B124s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B232 s
Keywords: (3GdfMhs